A Case of a Ruptured Sclerosing Liver Hemangioma. (31st May 2011) - Papafragkakis, Haris; Moehlen, Martin; Garcia-Buitrago, Monica T.; Madrazo, Beatrice; Island, Eddie; Martin, Paul
Abstract : Hemangiomas are the most common benign tumors found in the liver, typically asymptomatic, solitary, and incidentally discovered. Although vascular in nature, they rarely bleed. We report a case of a 52-year-old woman with a previously stable hemangioma who presented to our hospital with signs and symptoms indicative of spontaneous rupture. We review the literature, focusing on diagnosis and management of liver hemangiomas.